Early detection and prevention of domestic violence using the women abuse screening tool (WAST) in primary health care clinics in Malaysia - Wong, Y.L.; Othman, S. (SAGE Publications, 2008)
Despite being an emergent major public health problem, little research has been done on domestic violence from the perspectives of early detection and prevention. Thus, this cross-sectional study was conducted to identify domestic violence among female adult patients attending health centers at the primary care level and to determine the relationship between social correlates of adult patients and domestic violence screening and subsequent help/health-seeking behavior if abused. Face-to-face interviews were conducted with 710 female adult patients from 8 health centers in Selangor who matched the inclusion criteria and consented to participate in the study, using a structured questionnaire that included adaptation of a validated 8-item Women Abuse Screening Tool (WAST). Statistical tests showed significant differences in ethnicity, income, and education between those screened positive and those screened negative for domestic violence. Of the participants, 92.4 reported that during consultations, doctors had never asked them whether they were abused by their husband/partner. Yet, 67.3 said they would voluntarily tell the doctor if they were abused by their husband/partner. The findings indicate that primary care has an important role in identifying domestic violence by applying the WAST screening tool, or an appropriate adaptation, with women patients during routine visits to the various health centers. Such assessment for abuse could be secondary prevention for the abused women, but more important, it will serve as primary prevention for nonabused women. This approach not only will complement the existing 1-stop crisis center policy by the Ministry of Health that copes with crisis intervention but also will spearhead efforts toward prevention of domestic violence in Malaysia.